In Silico Study of Aptamer Specificity for Detection of Insulin as Development for Diabetes Mellitus Diagnosis - Mulyani, Dinda Exelsa; Maksum, Iman Permana; Yusuf, Muhammad (Universitas Gadjah Mada, 2024)
Diabetes mellitus (DM) is a metabolic disorder characterized by elevated blood glucose levels. There are 2 types of DM where molecular-level diagnosis becomes very important because both have different treatments to avoid treatment errors. An electrochemical aptasensor as a type 2 DM detector with insulin target has been developed. This study aims to determine the interaction and specificity based on the values of RMSD, RMSF, and binding energy between aptamer and insulin when it reaches stability in silico compared to HbA1c and glucose. Docking simulations were performed on the HDOCK webserver and dynamics simulations for 1000 ns on the aptamer and protein molecular models used. The simulation results were analyzed to see the stability and visualized using VMD to see the conformation of the aptamer-ligand complex. The docking result showed higher binding energy between aptamer-insulin compared to other molecules, namely −221.87 kcal/mol. The results of RMSF and RMSD analysis of molecular dynamics simulations show that the system is stable, has the best binding energy value of −9.9510 kcal/mol. The aptamer complex with insulin showed better specificity compared to glucose and HbA1c based on RMSD, RMSF, and binding energy.